Consolidation of thermoplastic coatings by means of a thulium-doped fiber laser - Wittmann, Alexander; Heberle, Johannes; Huber, Florian; Schmidt, Michael (Journal of Laser Applications, 2021)
Thermoplastic polymers such as polyamide 12 (PA12) are of great interest for functional coatings in industry due to their good material properties (e.g., chemical and wear resistance and biocompatibility). In order to provide a high local selectivity of polymer deposition and to shorten the process chain, a laser-based coating process represents a promising approach for generating functional coatings. In this work, a laser-based coating process for PA12 powder on stainless steel substrates is investigated experimentally by using a thulium-doped fiber laser with a wavelength of 1.94 μm. Due to the higher inherent absorption of the laser radiation in the powder material, a thulium-doped fiber laser is more appropriate for processing PA12 powder in comparison to more common near-infrared laser beam sources with wavelengths around 1 μm. The influence of the main process parameters (laser power, scanning speed, hatch distance, and substrate temperature) on the resulting coatings was evaluated. For this purpose, optical microscopic analyses were performed to characterize the coating surfaces and cross sections in terms of possible defects. In order to assess the adhesion between the coating and the substrate, cross-cutting values were determined. On the basis of the quality characteristics regarding the coating surface, a process window was determined to produce a closed melting film, which fully covers the metallic substrate. By an adjustment of the scanning speed (5 mm/s) and line overlap (50%/62.5%), a broadening of the process window could be achieved. An additional substrate heating (T ≥ 90°C) is an appropriate strategy, which enlarges the size of the process window significantly. Optical microscopy analyses and cross-cutting tests verified the suitability of a thulium-doped fiber laser for processing dense PA12 coatings with an adequate adhesion to the stainless steel substrate. The substrate temperature is a decisive process parameter to obtain a homogeneous morphology and to further improve the adhesion between the metallic substrate and PA12 layer.